The maritime engineering reference book a guide to ship design, construction and operation - Molland, Anthony F. (Butterworth-Heinemann, 2008)
The Maritime Engineering Reference Book is a one-stop source for engineers involved in marine engineering and naval architecture. In this essential reference, Anthony F. Molland has brought together the work of a number of the world's leading writers in the field to create an inclusive volume for a wide audience of marine engineers, naval architects and those involved in marine operations,insurance and other related fields. Coverage ranges from the basics to more advanced topics in ship design construction and operation.